Isolation and characterization of two satellite DNAs in some Iberian rock lizards (Squamata, Lacertidae). Issue 1 (6th September 2013) - Giovannotti, Massimo; Rojo, Verónica; Nisi Cerioni, Paola; González‐Tizón, Ana; Martínez‐Lage, Andrés; Splendiani, Andrea; Naveira, Horacio; Ruggeri, Paolo; Arribas, óscar; Olmo, Ettore; Caputo Barucchi, Vincenzo
ABSTRACT Satellite DNAs represent a large portion of all high eukaryotic genomes. They consist of numerous very similar repeated sequences, tandemly arranged in large clusters up to 100 million base pairs in length, usually located in the heterochromatic parts of chromosomes. The biological significance of satDNAs is still under discussion, but most of their proposed functions are related to heterochromatin and/or centromere formation and function. Because information about the structure of reptilian satDNA is far from exhaustive, we present a molecular and cytogenetic characterization of two satDNA families in four lacertid species. Two families of tandemly repeated DNAs, namely TaqI and HindIII satDNAs, have been cloned and sequenced from four species belonging to the genus Iberolacerta. These satDNAs are characterized by a monomer length of 171–188 and 170–172 bp, and by an AT content of 60.5% and 58.1%, respectively. FISH experiments with TaqI satDNA probe produced bright signals in pericentromeric regions of a subset of chromosomes whereas all the centromeres were marked by HindIII probe. The results obtained in this study suggest that chromosome location and abundance of satDNAs influence the evolution of these elements, with centromeric families evolving tenfold faster than interstitial/pericentromeric ones. Such different rates render different satellites useful for phylogenetic investigation at different taxonomic ranks. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 13–26, 2014. © 2013 Wiley Periodicals, Inc.